Territorio, hombres y ganadería en la región de Piura. La experiencia de la construcción social de las estancias ganaderas en el siglo XVIII - Espinoza Claudio, César (2015)
In this essay we approach a subject that has been little studied in Piura›s regional historiography: the man as an regional landscape modeller agent. We seek to describe characteristics of colonial geography related to a regional northern space, explore dynamics and flows of livestock (cattle) production farms, and study indigenous communities people. We synthesize a chapter of the «Piura’s Economic Report (1804)», written by don Joaquin de Helguero, in order to introduce you knowledge about ecological archipelagoes that were named at that time «Los Valles» (“The Valleys”), and also Piura’s mountains. Diversity exploration of variables tied to geographical dimensions and economy will allow us to enter in the knowledge of the conjuncture of regional crisis and the particular situation of the indigenous and highland companies that crosses this region after the FEN of 1791